Contemporary Approaches to EE: Place-Based Education and Urban EE. Correlation With John Pantis’ Work in EE - Καλαϊτζιδάκη, Μαριάννα (Education Sciences, 2020)
In this paper we present two contemporary approaches to Environmental Education, that we implement at the Department of Primary Education of the University of Crete. The first approach, place-based education, uses the local community and the local environment as context and content for teaching and learning and environmental action, with the ultimate goal of connecting students with their place. The second approach, urban environmental education, is environmental education in the cities where most of us live. Cities are seen as opportunities for learning and action with environmental education outcomes such as environmental literacy, sense of place, nature connected-ness, environmental stewardship and positive youth and community development. Both approaches are evident in Yannis Pantis’ work in Environmental Education presented in this issue. The transformation of the Aristotelian University of Thessaloniki campus into an Environmental Education park and the community vegetable gardens he initiated when he was Vice Dean, are excellent examples of Urban Environmental Education. On the other hand, his attachment to Zakynthos, his birth place, and the actions he took there (efforts for the establishment of the National Sea Park, and the supervision of 3 PhD theses in Environmental Education) confirm the literature on the relationship between place attachment and actions to protect that particular place.